KELAS IBU HAMIL TAHAP II DI DESA KENITEN - Indriani, Ririn; Titisari, Ira; Setyarini, Arika Indah (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Health development is essentially an effort carried out by all components of the Indonesian nation. It is hoped that the high maternal mortality rate during pregnancy, childbirth and postpartum in Kediri Regency can help pregnant women to detect high risks during pregnancy and increase mother's knowledge in understanding the signs and dangers of pregnancy. This also supports the joint movement program to reduce maternal and infant mortality in Kediri Regency. Focus group discussions as a method of providing education to mothers in class II pregnant, are effective for assessing mother's knowledge about danger signs and high-risk pregnancies. From the target of 15 pregnant women, the results showed that there was a significant increase in the results of the pre and post test scores given. Where the low score on the pre test is 20% on the post test not found (0,) on the post test value. the average score in the pre-test was 33.3%, the post-test remained 33.3%, while the high score in the pre-test was 46.67%, the post-test increased to 66.67%. So it can be concluded that the class of pregnant women using the focus group discussion method is effective in assessing maternal knowledge in detecting high-risk pregnancies.